Barriers in the implementation of IBS formwork in Malaysian construction industry - Siti Nur Syafiqah, Mohd Sa'don (2017)
Nowadays, in Malaysian construction industry, the use of IBS as a method of construction is develop rapidly, but not for this type of IBS; IBS formwork or prefabricated formwork. This research is to focal point the critical factors of implementation the used of Industrialized Building System (IBS) formwork or namely as pre-fabricated formwork system in the Malaysian construction industry. Based on the reviews of a previous research and related literature, this paper was identified five (5) main barriers and challenging criteria that classified as a difficulties to the success of IBS formwork system application; the issues related to product technical limitation, high initial cost & financial barriers, lack incentive & promotion guidance, less product support and lack exposure on IBS formwork were highlight as a key dimension for the uses of IBS formwork system to success. The objective of this paper is to investigate the practice of IBS formwork in Malaysian construction industry, determine barriers in implementation of IBS in Malaysian construction industry and to point out the main barriers in implementation of IBS formwork in Malaysian construction industry. Questionnaires survey was conducted in order to achieve the objectives. The respondents consisted of person who involved in construction project. The data were tabulated using Microsoft Excel and then analyzed using frequency analysis, average index and ranked. In conclusion, the barriers of IBS implementation in Malaysia has been identified and discussed. According to this research, product technical limitation, high initial cost & financial barriers and lack incentive & promotion guidance are the main barriers factor in IBS implementation in Malaysia.